The optimization of the enzyme immobilization methods for amperometric glucose biosensors - Aziz, Azila; Idris, Ani; Abd. Rahman, Badarulhisam (Universiti Teknologi Malaysia, 2004)
Enzyme immobilization method affects the performance of a glucose biosensor considerably. In this project, several methods of glucose oxidase immobilization for peroxide based amperometric glucose biosensor had been investigated. Parameters such as temperature, matrix concentration and cross-linker concentration were considered. For the first enzyme immobilization method, the effect of casting temperature on apparent enzyme activity was investigated. Glucose oxidase was immobilized in cross-linked poly(vinyl alcohol) at two different temperatures, 25oC and 4 oC. The membranes immobilized at 25 C showed higher enzyme activity after 25 days compared to membranes immobilized at 4oC. The membranes immobilized at 25 oC were also found to be able to retain enzyme better. For the second enzyme immobilization method, the effect of matrix concentration on apparent enzyme activity was investigated. Glucose oxidase was immobilized in cross-linked poly(vinyl alcohol) at two different PVA concentrations, 10% PVA and 15% PVA. With higher PVA concentration (15%), the enzyme retaining ability was better. However, the 10% PVA-GOD membranes performed better in terms of available enzyme activity. Enzyme activity of the 10% PVA-GOD membranes was approximately 33% higher than the 15% PVA-GOD membranes. For the third enzyme immobilization method, the effect of matrix concentration on apparent enzyme activity was once again investigated. However, this time physical enzyme immobilization method was considered. Glucose oxidase was immobilized in freeze-thawed PVA at three different PVA concentrations, 5% PVA, 10% PVA and 15% PVA. This work suggests that the higher the PVA concentration used for immobilization, the better the retention of the enzyme. Nevertheless, higher PVA concentration didn’t necessarily correlate well with enzyme activity. 10% freeze-thawed PVA-GOD membranes have the highest activities. The performances of 15% freeze-thawed PVA-GOD membranes and 5% freeze-thawed PVA-GOD was comparable. In terms of kinetic properties, PVA-GOD freeze-thawed membranes appprepared with 10% PVA exhibited the highest Kmapp compared to the others. This means that they are more suitable to be used as bio-recognition elements for glucose biosensors than the other two. For the fourth enzyme immobilization method, the effect of cross-linker concentration on apparent enzyme activity was investigated. Glucose oxidase was immobilized within silica sol/PVA and cross-linked with (3-glycidoxypropyldimethylethoxy)silane. For the membranes prepared with 1:1 (TMOS: 3GPDES), the percentage of enzyme activity which remained at day 40 was about 51%. Meanwhile, for the membrane prepared with 1:2 (TMOS: 3GPDES) and 1:3 (TMOS: 3GPDES), the percentage of enzyme activity which remained at day 40 app appwas 69% and 58%, respectively. Vmaxapp and Kmapp values for membranes prepared with 1:2 (TMOS: 3GPDES) were the highest indicating that it is most suitable to be used as the bio-recognition element for a glucose biosensor due to its stability and kinetic properties.